RAMBUT SEBAGAI ASPEK PENDISIPLINAN TUBUH PEREMPUAN: STUDI KASUS PADA BIKSUNI BUDDHA TANTRAYANA-TIBETAN - Izmy Khumairoh (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
This article tries to examine the fact that the biological determination between men and women contains the practice of disciplining the body that is formed due to social construction. Women's bodies tend to receive more control than men's because the image idealized of women. The body is then domesticated and gendered, and people lose their authority over their bodies. However, in everyday reality, there are some women voluntarily experience bodily discipline because they choose to live a celibate life. Thus, there is a friction between the femininity concept by societal standards and religious teachings, in this context is symbolized by the shaving of the head among female Buddhist monks. By shaving her head, instead of being considered less feminine, they look more divine. The case study of a female monk in the teachings of Tantrayana-Tibetan Buddhism also included to strengthen the analysis.